A spheroidal control volume for the quantitative measurement of regurgitant flow by cardiac MRI - Kortright, Eduardo; Rayarao, Geetha; Li, Longchuan; Anayiotos, Andreas; Biederman, Robert W.W.; Doyle, Mark (My University, 2008)
Purpose: We sought to show that a spheroidally shaped control volume (CV), formed from a minimal MRI data set, can be used to measure regurgitant flow through a defective cardiac valve consistently and accurately under a variety of flow conditions. Materials and Methods: Using a pulsatile flow pump and phantoms simulating severe valvular regurgitation, we acquired 31 scans of two or three radially oriented slices, using a variety of flow waveforms and regurgitant volumes of 12 to 55 ml. Data sets included high- and low-resolution scans, and variable-rate sparse sampling was also applied to reduce the scan time. An oblate spheroid was placed in the pump chamber opposite the jet and fit as tightly as possible to isomagnitude velocity contours at 25% of the velocity encoding limit. Results: Normalized regurgitant volumes (NRVs) expressed as a percentage of the pump setting were obtained from the product of the spheroid surface area with the velocities normal to it. Mean ± SD NRV values were 96.8 ± 6.6% for all scans. Imaging times in the breath-hold range were obtained using reduced resolution and variable-rate sparse sampling approaches without significant degradation in accuracy. Conclusion: In our preliminary findings, the spheroidal CV method showed clear potential for the development of a robust, clinically feasible technique for the measurement of regurgitant volume.
Keywords: Magnetic resonance imaging; Heart valves--Diseases; Apparitions; Image processing